If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 74 = 28 + V Solving 74 = 28 + V Solving for variable 'V'. Move all terms containing V to the left, all other terms to the right. Add '-1V' to each side of the equation. 74 + -1V = 28 + V + -1V Combine like terms: V + -1V = 0 74 + -1V = 28 + 0 74 + -1V = 28 Add '-74' to each side of the equation. 74 + -74 + -1V = 28 + -74 Combine like terms: 74 + -74 = 0 0 + -1V = 28 + -74 -1V = 28 + -74 Combine like terms: 28 + -74 = -46 -1V = -46 Divide each side by '-1'. V = 46 Simplifying V = 46
| 4j/12=-1 | | 72-w=8w | | y=rx+3 | | 13b=78 | | X-4=-9-4x | | 5n-2-7n=-14 | | 4x-18=3(2x-9) | | 7-2n=-13-6n | | 7.50p+2.50=12.50 | | 8x+3+4(x-5)= | | 5(r-5)-4(r-1)=2(r+4) | | 2M/(22M^2) | | 3x-2(4x-3)=6-(x+8) | | -7y+3=-22 | | y+2*-4=-6 | | 8w=27+5w | | 9x-2b+8b+3x= | | 3(4x+1)-2(2x-7)=73 | | 70-(3Q+70)=70-4Q | | 4x+5x-2=16 | | 4.5+y=y-5.5 | | 16x+17=73 | | X-(-2-x)=-2(-2x-4) | | 6x+5y=1650 | | 8=(y/3=3/4) | | 17u=48+9u | | −1/2s−7 | | (3n-6)-(4n-8)= | | 6.28r=3.14r^2 | | (2x^2+y)dy+(x^2y-x)dx=0 | | 3-(x+5)=2(x+3)-7 | | -84=-7(2m+6)+8m |